If they only knew : 60 anonymous true stories showcasing the power & perseverance of women - Regalado, Stephanie (SheSays Media, 2023)
"If They Only Knew is a powerful and heartfelt book that shatters the illusion that we understand what goes on in the lives of those around us. In this poignant collection, Stephanie Regalado shares the inspiration behind this book -- her own experience of attending a city hall meeting while in the midst of a miscarriage, highlighting the hidden struggles we often carry. Drawing from her extensive background as a journalist, Stephanie embarks on a journey of storytelling, encouraging readers to embrace vulnerability and openness. The book features a selection of 60 anonymous stories, shared with unwavering courage and honesty, from women who have faced their own hidden challenges. These narratives reveal the strength and resilience that emerge from adversity and concealment. At a time when the world is witnessing a seismic shift in the voices of women and their collective empowerment, If They Only Knew becomes a catalyst for change. It invites readers to explore the rich tapestry of female experiences, showcasing the diverse possibilities and fortitude that women possess. This book serves as an antidote to a culture that keeps secrets hidden and vulnerabilities suppressed, fostering unity and understanding. In a society where women's stories are more essential than ever If They Only Knew stands as a beacon of connection and empathy. It unearths the extraordinary power within each woman and the collective strength of sisterhood, ultimately empowering readers to embrace the full spectrum of their potential without judgment. If you've ever gazed at those around you and wondered what secrets they hold -- and wondering what they would think if they knew yours -- this book offers an opportunity to connect, share, and be inspired. It's a heartfelt call to women everywhere to contribute their own stories to continue this powerful movement." --Amazon.